DEFICIÊNCIA VISUAL: dificuldades e estratégias do professor no processo de inclusão escolar no ensino médio - BORGES, Tamires Coimbra Bastos (2016)
Inclusive education has been the subject of intense debate and theoretical productions from the 90s Taking a leading role in discussions of the urgent need to overcome the exclusion and the development of strategies for real inclusion of people with disabilities in the regular education system of the country. Therefore, this research seeks to insert themselves in these educational discussions and are based on quantitative and qualitative analysis, covering quantitative and qualitative methods, from a case study in a school of public schools in São Luis-MA. This research aims to analyze how teachers of mainstream education and specialized educational services are enabling the process of inclusion of students with visual impairment (blindness and low vision) in high school in Sao Luis, MA. The participants of this research form two groups of teachers: 8 teachers of regular schools and 2 teachers of specialized educational services that work in high school in a school public school in São Luís, with whom interviews were conducted semistructured. The data obtained from these interviews were analyzed based on the content analysis technique as proposed by Bardin (1979).The results of this analysis revealed that the main difficulties encountered during the process of school inclusion of students with visual impairment in regular high school were: lack of adequate training of teachers to meet the demands of school inclusion; inadequate infrastructure with limited materials and resources; disproportion between the number of students and teachers in class; difficulty of abstraction and to understand which activities use of vision is required; lack of awareness of nondisabled peers and prejudice; learning difficulties due to late entry into the regular school; need for another professional in the classroom; dialog absence among teachers. The results also revealed the perceptions of these teachers on their own strategies: the use of special tools and supplies for the Braille system learning as reglete, punch, Braille and Sorobã machine; constant dialogue with the Napnee and students with visual impairment; individualized attention to students with visual impairment in contraturno; interaction of students with visual impairment and other colleagues of the room; raise awareness among teachers; provide training for teachers of the regular room. It concludes that the difficulties and barriers encountered in everyday practice have hamstrung the guarantee of the right to inclusive education for students with visual impairment. However, although it admits the existence of these difficulties it was plausible initiatives of teachers of regular schools and educational specialized care through excellent teaching practices based on school inclusion of students with visual impairment, contributing to the school to which they belong is a state reference in serving the student with visual impairment in regular high school rooms.